Storage related changes in Lassi supplemented with Amaranthus flour - Patel, Arunkumar Chelabhai; Pandya, A J; Patel, R A; G, Gopikrishna; Shendurse, A M; Roy, S K (Indian Journal of Dairy Science, 2020)
The storage study of optimized Amaranthus lassi was carried out at refrigeration temperature (5 ± 2ºC) up to acceptable sensory level by the judges. After 21 days of storage at 5 ± 2ºC, the average flavour, body and texture, colour and appearance and overall acceptability score of lassi were significantly decreased. During 21 days of storage, the pH and acidity of lassi samples were significantly declined and increased, respectively with the progress of storage. The whey separation of lassi samples were significantly increased from 0.0 to 1.6 ml with change in storage period. The Standard Plate Count and Yeast and Mold Count of the lassi samples were non-significantly decreased and significantly increased respectively, during 21 days of storage. The developed lassi had shelf-life of 21 days.